Altitude and geographic coordinates in the ten-day mean minimum air temperature estimation in the State of Rio Grande do Sul, Brazil - Filho, Alberto Cargnelutti; Maluf, Jaime Ricardo Tavares; Matzenauer, Ronaldo; Stolz, Álvaro Prestes (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to estimate ten-day mean minimum air temperature (Tm) using altitude and the geographic coordinates latitude and longitude for the Rio Grande do Sul State, Brazil. Normal ten-day mean minimum air temperature of 41 counties in the State of Rio Grande do Sul, from 1945 to 1974 were used. Correlation analysis, path analysis of causal variables (altitude, latitude and longitude) on Tm, and parameters estimate of multiple linear regression equations were performed by the stepwise backward method, using Tm as dependent variable and altitude, latitude and longitude as independent variables, for the 36 ten-day periods of the year. Pearson's linear correlation coefficient between estimated and observed Tm, calculated for tem counties using data of the series of meteorological observations from 1975 to 2004 were used as independent data sets. The ten-day mean minimum air temperature may be estimated from the geographic coordinates in the State of Rio Grande do Sul. Altitude and latitude best explain the variation of the Tm.